Overcoming T790M mutant small cell lung cancer with the third‐generation EGFR‐TKI osimertinib. Issue 2 (6th December 2018) - Tang, Kejing; Jiang, Neng; Kuang, Yukun; He, Qiong; Li, Shuhua; Luo, Jiping; Jiang, Wenting; Chen, Yangshan; Sun, Yu; Chen, Lili; Chen, Yanyang; Zhu, Junfeng; et al.
Abstract : A large number of EGFR mutant non‐small cell lung cancer patients primordially benefit from first‐line treatment with first‐generation EGFR ‐ tyrosine kinase inhibitors (TKIs), such as gefitinib and erlotinib. However, multiple acquired resistance mechanisms have been described that limit the clinical efficacy of first‐generation EGFR‐TKIs. Herein, we report a rare case of lung adenocarcinoma harboring an EGFR exon 19‐deletion mutation before the administration of target therapy. This patient acquired resistance to first‐generation EGFR‐TKIs through small cell lung cancer (SCLC) transformation accompanied by the T790M mutation. Unexpectedly, this SCLC patient maintained a sensitive response to the third‐generation EGFR‐TKI osimertinib. This special case may indicate that osimertinib represents an effective target drug for SCLC patients who harbor an EGFR T790M mutation.